Care for an elderly person after lower limb amputation - Prylińska, Monika; Husejko, Jakub; Kwiatkowska, Klaudia; Wycech, Alicja; Kujaciński, Marcin; Rymarska, Olga; Sarnowska, Joanna; Rogala, Dorota; Jarosz, Karol; Nieciecka, Adrianna; et al. (Journal of Education, Health and Sport, 2019)
Introduction: Although currently less major amputation is performed, due to more effective revascularization and endovascular treatment, limbs amputations are still necessary and commonly used as a therapeutic method. Amputation of the lower limb is associated with long-term hospitalization, treatment, rehabilitation and a high level of mortality among older people. For the elderly, additionally suffer from number of chronic diseases, who for various reasons amputation of the limb is the only possible treatment option, recommendations regarding further care after such surgery are important. Results: Causes of lower limb amputation include ia. non-traumatic reasons like diabetes or infection and traumatic ones. Frequency of removal of the lower limb, regardless of its reason is estimated about 5.6 to 600 per 100,000 people and the percentage is about 20 times higher in diabetes-suffering people than in non-diabetic. In the case of this disease, amputations mainly concern men over 60 years of age, as well as people who have been subject to hospital treatment many times. Care for a patient who is prepared to amputation procedure include pre- and post-operative rehabilitation, prosthesis of amputated limb, psychological care, patient education and also pharmacotherapy. It is important to give to patient enoxaparin to reduce thromboembolic risk. To increase quality of life after amputation it is important to provide adequate nursing care. Discussion: Other overlooked diseases, which can lead to lower limb amputation are ia. Charcot disease. Proper diagnosis, differentiation and treatment process is extremely important cause can allow patient to avoid the amputation. Conclusion: Gathered recommendations for correct, high-quality, multi-faceted medical care for patients after amputation of the lower limb will improve the quality of medical services for this group of patients.